Teacher's intervention in providing understanding of association limits to girls (Cases in children who have stepfathers) - Kamil, Nurhusni; Zahrah, Faiqatuz; Dewi, Utami Kumala (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
Self-protection of children needs to be introduced from an early age in order to prevent unwanted things from happening. Thus it needs adult intervention in this case. The adults in question are teachers when they are at school and parents when they are at home. One form of protection and understanding of concepts that teachers need to introduce is boundaries in association. Association is not only limited to friendships that occur between boys and girls but also interactions that exist between children who have stepfathers. The stepfather as a foreign individual around the child because he does not have direct blood ties therefore they should not interact too intensely with the child. But that doesn't stop the stepfather from being close to his stepdaughter either. This study discusses the teacher's intervention in providing an understanding of the limits of association in girls with their stepfather. The type of research used is qualitative with a case study approach. Data collection techniques used in-depth interview techniques and unstructured questions which were carried out together with teachers at the school. The sample in this study was 1, 5-year-old girl with the initials FA. The results of the research show that there are several efforts by teachers to provide an understanding to children about the boundaries of interacting with stepfathers, namely introducing the concept of stepfathers first to children, then the teacher invites children to have direct interactions in class such ass telling stories which are then interspersed with several questions.